Synchronization of ovulation in crossbred dairy heifers using gonadotrophin-releasing hormone agonist, prostaglandin F2a and human chorionic gonadotrophin or estradiol benzoate - Castilho, C. [UNESP]; Gambini, A.L.G. [UNESP]; Fernandes, P. [UNESP]; Trinca, L.A. [UNESP]; Teixeira, A.B. [UNESP]; Barros, C.M. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2000)
Girolando (Gir x Holstein) is a very common dairy breed in Brazil because it combines the rusticity of Gir (Bos indicus) with the high milk yield of Holstein (Bos taurus). The ovarian follicular dynamics and hormonal treatments for synchronization of ovulation and timed artificial insemination were studied in Girolando heifers. The injection of a gonadotrophin-releasing hormone (GnRH) agonist was followed 6 or 7 days (d) later by prostaglandin F2a (PGF2a). Twenty-four hours after PGF2a injection either human chorionic gonadotropin (hCG, GPh-d6 and GPh-d7 groups) or estradiol benzoate (EB, GPE-d6 and GPE-d7 groups) was administered to synchronize ovulation and consequently allow timed artificial insemination (AI) 24 and 30 h after hCG and EB injection, respectively. Follicular dynamics in Girolando heifers was characterized by the predominance of three follicular waves (71.4%) with sizes of dominant follicles (10-13 mm) and corpus luteum (approximately 20 mm) similar to those for Bos indicus cattle. In the GnRH-PGF-hCG protocol, hCG administration induced earlier ovulation (67.4 h, P<0.01) compared to the control group (GnRH-PGF) and a better synchronization of ovulation, since most of it occurred within a period of 12 to 17 h. Pregnancy rate after timed AI was 42.8 (3/7, GPh-d6) to 50% (7/14, GPh-d7). In contrast, estradiol benzoate (GnRH-PGF-EB protocol) synchronized ovulation of only 5 of 11 heifers from the GPE-d7 group and of none (0/7) from the GPE-d6 group, which led to low pregnancy rates after timed AI (27.3 and 0%, respectively). However, since a small number of Girolando heifers was used to determine pregnancy rates in the present study, pregnancy rates should be confirmed with a larger number of animals.
Keywords: follicle; corpus luteum; ovulation; hCG; GnRH; artificial insemination